2006
DOI: 10.1210/jc.2005-2420
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Adrenalectomy for Potentially Malignant Adrenal Tumors Greater than 5 Centimeters

Abstract: LA is a reasonable option for selected large adrenal tumors when complete resection is technically feasible and there is no evidence of local invasion. Hand-assisted LA is a good alternative to open conversion if a difficult dissection is encountered intraoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 19 publications
3
30
0
7
Order By: Relevance
“…Likewise, authors from Taiwan reported 39 patients with tumours > 5 cm (mean 6.2 cm), eight of which were malignant (four cortical carcinomas and four metastatic tumours) and were subsequently removed laparascopically. The diaphragm was perforated in one case, pneumonia developed in another one, and the wound was infected in three patients (19).…”
Section: Discussionmentioning
confidence: 97%
“…Likewise, authors from Taiwan reported 39 patients with tumours > 5 cm (mean 6.2 cm), eight of which were malignant (four cortical carcinomas and four metastatic tumours) and were subsequently removed laparascopically. The diaphragm was perforated in one case, pneumonia developed in another one, and the wound was infected in three patients (19).…”
Section: Discussionmentioning
confidence: 97%
“…Liao et al reported that they preferred open surgery for masses greater than 8 cm which would create difficulties in their dissection, and hemostatic control. [16,17] However with increasing expertise in recent years, size of the mass is no longer an indication for open surgery, and various authors have reported their laparoscopic adrenalectomy experience for larger adrenal masses. [18] Nowadays, for laparoscopic adrenalectomy, four different techniques as lateral transperitoneal, anterior transperitoneal, transthoracic, and posterior retroperitoneal techniques have been described.…”
Section: Discussionmentioning
confidence: 99%
“…From the surgical point of view, laparoscopic adrenalectomy, whether robot-assisted or not, is now a wellestablished procedure with a low complication rate [1,2,20,[23][24][25][26]. In many cases, it would seem sensible to err on the side of caution and excise the tumour even if all malignant criteria are not fulfilled.…”
Section: Discussionmentioning
confidence: 99%